Movement Games in Various Kinds of Sport (Experiences of Coaches Studying at Lase) (Baltic Journal of Sport and Health Sciences, 2015)
Background. Practice game contributes to the development of coordinated motor skills needed for later game playing or sport. When coaches know and use movement games corresponding to the specific sport to increase athlete’s interest and pleasure about sport and sport pedagogue’s knowledge about the scientifically based movement games, they promote the acquisition of skills at higher levels. Research aim was to ascertain the knowledge of coaches about movement games in sport classes, in order to research the use of movement games in the training process in different sports and to investigate how games are applied in the training process in Latvia.Methods.  The  methods  of  research  were  analysis  of  the  literature  corresponding  to  the  research  problem, questionnaire and discussions with coaches, statistical methods. The study was conducted in 2010 – 2012 in Riga, LASE. There were 96 research participants – simultaneously practicing coaches and the extramural students of the LASE.Results.  In  the  study  process  we  investigated  and  evaluated  the  knowledge  of  coaches  and  their  opinions  regarding movement games: development of physical abilities, improvement of the sport technique, development of social skills, and the experience in using movement games in training classes. Responses to the first three questions were compared with those obtained in the questionnaire survey in 1994.Conclusions. The questionnaire survey showed that coaches were willing to apply movement games. Some of them also were sceptic about using movement games in sport activities; 94% admitted that games facilitated physical abilities, 87.5% agreed that games aided in the development of sport techniques, and 85% of respondents were confident that games contributed to building up social skills. In the questionnaire of 1994, the number of those who considered that games were essential in training was similar to those in the questionnaire survey of 2012 – respectively 80 and 84%. In total, movement games were applied by 61% of different sports coaches (1994) in comparison with 79% today. Changes in indices were statistically significant (p < .05). Even 18% more respondents gave preference to games in the questionnaire survey of 2012 than in the questionnaire survey of 1994.Keywords: coaches, questionnaire survey, knowledge, movement games.